β-Carotene supplementation results in adverse ventricular remodeling after acute myocardial infarction - Zornoff, Leonardo Antonio Mamede [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Campana, Alvaro O.; Paiva, Sergio Alberto Rupp de [UNESP] (Elsevier, 2006)
Objective: We studied the effects of β-carotene (BC) on ventricular remodeling after myocardial infarction. Methods: Myocardial infarction was induced in Wistar rats that were then treated with a BC diet (500 mg/kg of diet per day; MI-BC; n = 27) or a regular diet (MI; n = 27). Hearts were analyzed in vivo and in vitro after 6 mo. Results: BC caused decreased left ventricular wall thickness (MI = 1.49 ± 0.3 mm, MI-BC = 1.23 ± 0.2 mm, P = 0.027) and increased diastolic (MI = 0.83 ± 0.15 cm2, MI-BC = 0.98 ± 0.14 cm2, P = 0.020) and systolic (MI = 0.56 ± 0.12 cm2, MI-BC = 0.75 ± 0.13 cm2, P = 0.002) left ventricular chamber areas. With respect to systolic function, the BC group presented less change in fractional area than did controls (MI = 32.35 ± 6.67, MI-BC = 23.77 ± 6.06, P = 0.004). There was no difference in transmitral diastolic flow velocities between groups. In vitro results showed decreased maximal isovolumetric systolic pressure (MI = 125.5 ± 24.1 mmHg, MI-BC = 95.2 ± 28.4 mmHg, P = 0.019) and increased interstitial myocardial collagen concentration (MI = 3.3 ± 1.2%, MI-BC = 5.8 ± 1.7%, P = 0.004) in BC-treated animals. Infarct sizes were similar between groups (MI = 45.0 ± 6.6%, MI-BC = 48.0 ± 5.8%, P = 0.246). Conclusion: Taken together, these data suggest that BC has adverse effects on ventricular remodeling after myocardial infarction. © 2006 Elsevier Inc. All rights reserved.
Keywords: Antioxidants; Fibrosis; Hypertrophy; Myocardial function; Ventricular dilation; beta carotene; acute heart infarction; animal experiment; animal tissue; chromatography; controlled study; diastolic blood pressure; heart ventricle remodeling; in vitro study; in vivo study; male; morphometrics; nonhuman; priority journal; rat; systolic blood pressure; vitamin supplementation; Animals; beta Carotene; Dietary Supplements; Heart; Male; Myocardial Infarction; Myocardium; Random Allocation; Rats; Rats, Wistar; Treatment Outcome; Ventricular Function; Ventricular Remodeling; Animalia; Rattus norvegicus